Recovery of Children from Acute Lower Respiratory Tract Infection(Pneumonia and Bronchiolitis) : In a tertiary Care Hospital - Sultana, Naima; Mollah, Md Abid Hossain; Kabir, ARM Luthful; Saha, Bithi Rani; Sarker, Aditi; Roy, Sunirmal; Jahan Kabir, Shah Mohd Eftar (Sir Salimullah Medical College Journal, 2022)
Backgrounds: Children are mostly the victims of pneumonia and bronchiolitis for which they are often hospitalized. Acute respiratory infection(ARI)results in 1.9 million deaths per year in developing countries(Taneja et. al 2009). It is important to know the recovery time of individual acute lower respiratory tract infection (ALRTIs) like pneumonia and bronchiolitis for better understanding the clinical feature and outcome. Knowing the length of stay (LOS) in case of ALRTI has not yet been worked out and studied well. Objective: To determine the recovery of different clinical features Length of hospital Stay and outcome of two common LRTIs viz pneumonia and bronchiolitis. Methods: A cross-sectional analytical study was done in department of pediatrics of Dhaka Medical College Hospital during the from October 2013 to September 2014. Cases were selected according to selection criteria. Pneumonia was diagnosed on the basis of fever, cough, breathing difficulty, and found chest indrawing, fast breathing, and bronchial breath sound or crackles on examination and consolidation or patchy opacity in chest X-ray and bronchiolitis on the basis of presence of runny nose followed by cough, breathing difficulty and wheeze on auscultation in a child below 2 yrs. Cases of pneumonia were treated with standard protocol of WHO and cases of bronchiolitis were treated with national guideline. The cases were followed up 12 hourly for 8 days using case collection sheet by monitoring 17 clinical features. Results : There were 54 cases of pneumonia and 54 cases of bronchiolitis. Baseline selected clinical-sociodemographic parameters of both the cases were similar in terms of sociodemographic status and some clinical features. The following clinical features were similar in both groups viz. cough(100% vs 100%) breathing difficulty (100%vs 100%), feeding difficulty (92.6%vs96.3%), chest indrawing(92.6%vs 96.3%).The dissimilar clinical features were fever (100%vs77.8%, p<0.001), runny nose (40.7%vs 100%, p<0.001%) sleeping difficulty (92.6% vs 77.8% p<0.03) wheeze (29.6% vs 100%, p<0.001) crackles(100% vs 18.5%, p<0.001). Dynamics of improvement in clinical features:Significant number of cases of pneumonia did not improve from breathing difficulty (40.7%) , feeding difficulty(40.7%), restlessness(16.7%), sleeping difficulty(76.9%), chest indrawing (63%), documented fever(54%) within 3 days, but more than 90% cases of bronchiolitis recovered from above mentioned clinical features. (P<0.001). Social smile returned to only 68% in case of pneumonia but 100% cases of bronchiolitis(p<0.001) with in 4 days. Conclusion: This study was concluded that almost 89% cases of pneumonia and 100% cases of bronchiolitis recovered. Length of hospital stay(LOS) was 5.8±2.1 days in pneumonia and LOS was 3.2±0.7 in bronchiolitis. Mortality was higher in cases pneumonia (3.7%) than cases of Bronchiolitis(0.0%). Sir Salimullah Med Coll J 2021; 29(2): 124-131